The Concise companion to language assessment (Hoboken, New Jersey : Wiley-Blackwell, 2025)
"The field of language assessment is an active and ever-changing field of applied linguistics scholarship. With interconnections with many linguistic subfields--from language teaching to language policy to the sociolinguistics of immigration--language assessment has a real, measurable impact on the lives of language learners, both in the contexts of first and foreign language learning. In an increasingly globalized world, language assessment must continue to evolve in concert with the needs of language learners worldwide. First published in 2014, The Companion to Language Assessment was the first works of its kind. As a four-volume major reference work, it brought together the full field of language assessment into a comprehensive resource that examined all aspects of language assessment across 35 world languages. Building upon the success of the major reference work, The Concise Companion to Language Assessment will collect a selection of some of the most popular chapters from the full work, along with a large selection of wholly new chapters, in a single-volume edition for undergraduate, post-graduate, and graduate students studying language assessment, language teaching and learning, TESOL, second language acquisition, language policy, and other related fields. The Concise Companion accounts for the most recent changes in the field through an increased focus on technology in language assessment and classroom-based assessment, with new coverage of learning-oriented assessment, teacher-based assessment, teacher assessment literacy, writing, pronunciation, speaking, plurilingual assessment, assessment for immigration, and many others. The Concise Companion will also include an almost entirely new selection of articles on innovations in assessment, and throughout the work, new emphasis will be placed on the impacts of colonialism and discrimination on the history of language assessment. In 56 chapters--29 of which will be new-- The Concise Companion to Language Assessment will provide an ideal reference for students pursuing degrees in applied linguistics who are interested in working in language assessment, education, and policy. It is sure to become a standard recommended text for the next generation of applied linguistics students"-- Provided by publisher
Includes bibliographical references and index.
Keywords: Language and languages -- Ability testing; Language and languages -- Examinations; Essays